Improving achievable traffic load of cognitive wireless networks under GoS constraints - Liang YU; Tao JIANG; Yang CAO (Tongxin xuebao)
To improve the achievable traffic load of secondary user(SU) under grade of service (GoS) constraints in cognitive wireless networks with heterogeneous traffic,a novel spectrum sharing scheme was proposed.The key idea of the proposed scheme was to introduce preemptive priority and buffering mechanism for real-time traffic and non-real-time traffic,respectively,according to their different delay characteristics.The proposed scheme could reduce the forced termination probability and the blocking probability for heterogeneous calls simultaneously.Numerical results show that the proposed scheme can effectively improve the achievable traffic load of SUs under GoS constraints.